Reversion of developmental mode in insects: evolution from long germband to short germband in the polyembrionic wasp Macrocentrus cingulum Brischke - Sucena, Élio (2017)
The deposited article is a post-print version and has peer review. This publication hasn't any creative commons license associated. There is no public supplementary material available for this publication.